2022
DOI: 10.21294/1814-4861-2022-21-6-68-80
|View full text |Cite
|
Sign up to set email alerts
|

Changes in blood monocyte functional prof le in breast cancer

Abstract: The purpose of the study was to identify functional features of circulation monocytes in patients with nonmetastatic breast cancer.Material and Methods. The study cohort consisted of 10 breast cancer patients treated at Tomsk Cancer Research Institute. 7 healthy female volunteers were enrolled as a control group. CD14+16-, CD14+16+ and CD14-16+ monocytes subsets were obtained from blood by sorting. Whole transcriptome profling was provided in monocytes from patients and healthy females. Macrophages were differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…As a result, monocytes are programmed to support breast tumor growth. [222,238,239] BC patients demonstrate elevated expression levels of the CD163 receptor on CD14 + 16 + and CD14 − 16 + monocyte populations, and its content also increases in TME after preoperative chemotherapy. [222] Reduced expression of MHC II in these monocyte populations is associated with a poor response to chemotherapy in BC [222,240]…”
Section: Circulating Monocytes In Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, monocytes are programmed to support breast tumor growth. [222,238,239] BC patients demonstrate elevated expression levels of the CD163 receptor on CD14 + 16 + and CD14 − 16 + monocyte populations, and its content also increases in TME after preoperative chemotherapy. [222] Reduced expression of MHC II in these monocyte populations is associated with a poor response to chemotherapy in BC [222,240]…”
Section: Circulating Monocytes In Breast Cancermentioning
confidence: 99%
“…[256,257] In vitro experiments also demonstrate that the macrophages derived from monocytes of BC patients can support tumor growth. [238] M2 TAMs are important for the development of BC metastases. Studies in breast cancer models have demonstrated that TAMs can promote metastasis by participating in extracellular matrix remodeling.…”
Section: Tumor-infiltrating Monocytes/macrophages In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation